La rançon du serment - Mathieu Tillier; Naïm Vanthieghem (Revue des Mondes Musulmans et de la Méditerranée)
This article presents the record of proceedings from the court of Ṭalīt, a village in the southern Fayyūm. The document, which dates from the reign of caliph al-Ḥākim, records an amicable settlement between a Muslim and a Christian regarding repayment of a debt. The text provides valuable information about the complex relationships between Ṭalīt and the neighbouring town of Ṭuṭūn, and exemplifies the procedure by which, according to several legal schools, a defendant could avoid taking an oath by paying his adversary a settlement.